2006
DOI: 10.1074/jbc.m510249200
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and Estradiol Interact with the Flavin Mononucleotide Site of Complex I Leading to Mitochondrial Failure

Abstract: This study evaluated the action of tamoxifen and estradiol on the function of isolated liver mitochondria. We observed that although tamoxifen and estradiol per se did not affect mitochondrial complexes II, III, or IV, complex I is affected, this effect being more drastic (except for state 4 of respiration) when mitochondria were coincubated with both drugs. Furthermore, using two respiratory chain inhibitors, rotenone and diphenyliodonium chloride, we identified the flavin mononucleotide site of complex I as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 51 publications
5
83
1
Order By: Relevance
“…Similarly, Wang and collaborators (2006) using human neuroblastoma SK-N-SH cells as experimental model, reported that E2 effectively reduce lipid peroxidation induced by 5-min H 2 O 2 exposure. Moreover, the authors observed that the estrogen receptor antagonist fulvestrant (ICI 182,780) did not block the effects of E2 (Wang et al, 2006) supporting previous findings from our laboratory indicating that the effects of E2 on liver mitochondria are estrogen-receptor independent (Moreira et al, 2006). Although we observed that E2 exerts a strong protective effect against lipid peroxidation (Figs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly, Wang and collaborators (2006) using human neuroblastoma SK-N-SH cells as experimental model, reported that E2 effectively reduce lipid peroxidation induced by 5-min H 2 O 2 exposure. Moreover, the authors observed that the estrogen receptor antagonist fulvestrant (ICI 182,780) did not block the effects of E2 (Wang et al, 2006) supporting previous findings from our laboratory indicating that the effects of E2 on liver mitochondria are estrogen-receptor independent (Moreira et al, 2006). Although we observed that E2 exerts a strong protective effect against lipid peroxidation (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…These data are supported by a previous in vitro study from our laboratory that showed that lower concentrations of TAM that do not interfere with mitochondrial function, in the presence of E2 significantly affect the function of these organelles. Furthermore, we were able to show that TAM and E2 act directly on the flavin mononucleotide (FMN) site of complex I leading to mitochondrial failure (Moreira et al, 2006). Although these results were obtained with liver mitochondria isolated from male rats, preliminary results from our laboratory show the same effects in mitochondria isolated from female rats though less pronounced.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Tamoxifen alone destabilizes the mitochondria to generate ROS, which agrees with previous studies that state that the drug can directly target the mitochondria. 14,15 In a previous study, we have shown that the mitochondria of melanoma A375 cells are vulnerable to tamoxifen treatment, thereby sensitizing these cells to co-treatment. 16 curcumin promoted rapid dissipation of the mitochondrial membrane potential in HeLa cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
“…Different inhibitors of complex I (for example, tamoxifen; Moreira et al, 2006), complex II (for example, fenretinide; Cuperus et al, 2010) or complex III (for example, adaphostin; Le et al, 2007) markedly induce ROS and apoptosis in tumour cells. One of the most promising drugs in this field is the vitamin E derivative a-tocopheryl succinate (Dong et al, 2007(Dong et al, , 2008(Dong et al, , 2009) and its mitochondrial targeted analogue mitoVES (Dong et al, 2011a, b) developed by the Neuzil group.…”
Section: Rc-based Strategies In Cancer Therapy?mentioning
confidence: 99%